Rumination Antara Usia Remaja Dan Dewasa - Faizah Faizah; Nisrina Purnomo (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
The aim of  this research to understanding rumination between adolescents and adults. This study refers to the dimensions of rumination such as brooding and reflection presented by Treynor, Gonzales, and Nolen-Hoeksema.  The subjects in this study are divided into two groups, The first group is the age of adolescents with 101 subjects and the second group is the age of adults with 105 subjects. Determination of subjects using incidental sampling. Data collection techniques are carried out with questionnaires named Ruminative Responses Scale (RRS). The collected data were analyzed using independent sample t test. The results showed that there were differences of ruminations between adolescents and adults. The results also showed that the adolescents group had higher rumination than the adults group.